Association between Children's Physical Activity and Parental Practices Enhancing Children's Physical Activity: The Moderating Effects of Children's BMI z-Score - Liszewska, Natalia; Scholz, Urte; Radtke, Theda; Horodyska, Karolina; Liszewski, Michal; Luszczynska, Aleksandra (Frontiers in Psychology, 2018)
Objective: Parental practices that aim at increasing children’s physical activity (e.g., modelling, support) are known to be related to children’s physical activity. So far, however, the association between these two sets of variables was studied without considering the role of child BMI z-score, which may determine the effectiveness of parental practices. The present study aims at filling this void. Design: Longitudinal data were collected among 879 dyads of children (6-11 years old) and their parents. Parental physical activity practices (measured among parents), physical activity, body mass and height (measured among children) were assessed twice (at baseline and 7-month follow-up). Body mass and height were measured objectively. Seven moderation analyses were conducted. Results: Six parental practices emerged to be especially relevant for the physical activity of the children: collaborative social control, overall support, stimulation to be active, general encouragement to physical activity, positive social control and modeling. Children’s BMI z-score was significant moderator in few associations. The relationships between parental positive social control, overall parental support, and general parental encouragement to physical activity and children’s physical activity at the follow-up were significant among children with low and medium Bmi z-score only. In turn, collaborative social control, and modelling predicted children’s physical activity at the follow-up regardless child’s Bmi z-score. Conclusions:. Among children with low BMI z-score the more often parents were using most of the practices the more likely their children were physically active. Otherwise parental positive social control or overall parental support may be ineffective in children with higher body mass who are in particular need to increase their physical activity